2010
DOI: 10.1016/j.envres.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to the major DDT metabolite 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (DDE) and growth in boys from Mexico

Abstract: Recent data suggest that prenatal exposure to p,p'-DDE may reduce height and increase body mass index (BMI) in childhood, thus potentially raising the risk of adult health problems. The association between prenatal DDE exposure and growth was evaluated in 788 boys from Chiapas, an area of Mexico where DDT was recently used. The median DDE levels in maternal serum at birth (2002)(2003) were 2.7 μg/g lipid. 2,633 measurements of height (cm) and weight (kg) were obtained in [2004][2005]. The median age of the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 46 publications
10
61
3
3
Order By: Relevance
“…In the present study, however, DDE did not µg/L CPP (1959-1965) NHANES (2003 show an interaction with maternal smoking or prepregnancy BMI. Similar to our results, two previous studies that assessed prenatal exposure to p,p´-DDT in relation to BMI also reported null findings among infants and youth (Cupul-Uicab et al 2010;Gladen et al 2004) (see Supplemental Material, Table S7). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, however, DDE did not µg/L CPP (1959-1965) NHANES (2003 show an interaction with maternal smoking or prepregnancy BMI. Similar to our results, two previous studies that assessed prenatal exposure to p,p´-DDT in relation to BMI also reported null findings among infants and youth (Cupul-Uicab et al 2010;Gladen et al 2004) (see Supplemental Material, Table S7). …”
Section: Discussionsupporting
confidence: 92%
“…A summary of prior studies assessing prenatal exposure to β-HCH, p,p´-DDE, p,p´-DDT, HCB, and PCBs in relation to body weight or BMI is presented in Supplemental Material, Table S7. Similar to previous studies conducted among subjects who experienced relatively high exposure, prenatal exposure to p,p´-DDE was not associated with BMI (Cupul-Uicab et al 2010;Gladen et al 2004) (see Supplemental Material, Table S7). Earlier studies that reported an association between DDE exposure and higher BMI during infancy and childhood (Mendez et al 2011;Valvi et al 2012;Verhulst et al 2009) had median levels of p,p´-DDE that were lower than or close to the lowest level of exposure found in the CPP participants (lowest value of p,p´-DDE in the CPP, 0.34 μg/g lipid).…”
Section: Discussionsupporting
confidence: 84%
“…The present analysis was based on a birth cohort of mothers and their singleton newborn sons from the State of Chiapas, Mexico; the cohort has been described in detail previously (Cupul-Uicab et al 2008; Cupul-Uicab et al 2010). Briefly, 870 healthy newborn males (born at term with normal birth weight) and their mothers were enrolled between 2002 and 2003 at the time of delivery.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Pan et al during year 2010 in USA, the breast milk levels of these pollutants and also children's blood levels were measured, thereafter height growth charts were evaluated, and results did not show a significant association (50). Five other similar studies reported the same results (6,8,9,13,25). However, Burns et al (2011) reported a significant association between children short stature and exposure to PCB, PBB, P,P'-DDT, and Dioxin (11).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that exposure to P, P' -DDT, DDE, and PBB did not affect height growth rate (6,13). In another study, the significant effect of dioxin on height growth was shown (11).…”
Section: -Hydroxypyrene (1 -Ohp)mentioning
confidence: 95%